Audel automated machines and toolmaking - Miller, Rex (Audel machinist's library., 2004)
Review Questions; Chapter 6: Dies and Diemaking; Cutting or Punching Dies; Shaping Dies; Combination Punching and Shaping Dies; Diemaking Operations; Summary; Review Questions; Chapter 7: Grinding; Cylindrical Grinders; Centerless Grinders; Internal Grinding; Surface Grinders; Cutter and Tool Grinding; Barrel Finishing (Abrasive Tumbling); Summary; Review Questions; Chapter 8: Laps and Lapping; Laps; Lapping Operations; Honing; Summary; Review Questions; Chapter 9: Toolmaking Operations; Introduction; Allowances and Tolerances; Layout; Summary; Review Questions.